New species, notes and new records of Trichogramma (Hymenoptera: Trichogrammatidae) in Brazil - Querino, Ranyse B.; Mendes, Jaci V.; Costa, Valmir A.; Zucchi, Roberto A. (Zootaxa, 2017)
Two new species of Trichogramma are described: Trichogramma piracicabense sp. nov. and T. valmiri sp. nov. Additionally, T. manicobai from eggs of the cassava hornworm Erinnyis ello is redescribed, and new records on the distribution and host associations of species of Trichogramma from Brazil are presented.